The effect of a gene associated with retinoid-interferon-induced mortality 19 (GRIM-19) on STAT3-induced gene expression in renal carcinoma. (29th June 2018) - Cui, Lingang; Meng, Qingjun; Wen, Jianguo; Yan, Zechen; Gao, Zhan; Tian, Yudong; Xu, Pengchao; Lian, Pengchao; Yu, Haizhou
Abstract: This study aimed to investigate the exact regulatory mechanisms of retinoid-interferon-induced mortality 19 (GRIM-19) in renal carcinoma. Tumour tissue samples from patients with renal carcinoma ( n = 30, there were seven cases of Stage I, eight cases of Stage II, eight cases of Stage III, seven cases of Stage IV) and control subjects were selected from adjacent normal tissue ( n = 10). Real-time quantitative PCR and western blotting were used to assess the level of GRIM-19, signal transducer and activator of transcription-3 (STAT3) and its downstream molecules. CD31 was detected by immunohistochemistry. The MTT assay was used to measure cell proliferation. The amount of apoptosis cells was analysed by Flow cytometry. The results showed that expression of GRIM-19 was decreased in renal carcinoma. However, in tumour tissue, STAT3 and its downstream signalling molecules showed the higher expression compared with control. Overexpression of GRIM-19, inhibited tumour growth apoptosis by mediating activators of STAT3 signal. In addition, interferon-β and all-trans-retinoic acid inhibited the renal carcinoma cell growth and induced apoptosis, and effect of drug combinations was particularly evident. In conclusion, GRIM-19 expression is associated with hyperactivation of STAT3-induced gene expression in renal carcinoma.